Biological and biochemical characterization of M2B cells: Classical BSE prion is conserved in transgenic mice overexpressing bovine prion protein gene. Issue 6 (2nd November 2017) - Suh, Tae-Young; Roh, In Soon; Kim, Hyo-Jin; Griffiths, Peter C.; Park, Kyung Je; Park, Hoo Chang; Hope, James; Kang, Hae Eun; Kim, Dae-Yong; Sohn, Hyun Joo
ABSTRACT: M2B cells with persistent classical bovine spongiform encephalopathy (C-BSE) have been established previously. In this study, we performed strain characterization of the M2B cell line in bovine PrP C overexpressing mice (Tg 1896). Mice intracranially inoculated with M2B cells and C-BSE survived for 451 ± 7 and 465 ± 31 d post inoculation, respectively. Although biochemical properties, including deglycosylation and conformational stability, differed between M2B cells and C-BSE, inoculation with M2B cell lysate and C-BSE resulted in comparable phenotypes. Comparable vacuolation scores and PrP Sc depositions were observed in the brain of Tg 1896 inoculated with both M2B cell lysate and C-BSE. Our results show that biochemical and biological characteristics of M2B cells and C-BSE are classifiable in the same strain.